Meningkatkan Kemandirian Dengan Metode Discovery Learning Berbantuan Lkpd Materi Manusia Sebagai Pribadi Fase E Kelas X Sma Negeri 1 Putussibau Kab Kapuas Hulu - Raimundus Aladim; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
There is a problem that firstly students are not actively involved in learning, so they face difficulties in understanding and applying the concepts being taught. Second, there is a mismatch between the learning methods used and the material being taught. And third, in the learning process so far, teachers have not associated the dimensions of the Pancasila Student Profile significantly in learning. So this research aims to: 1) Increasing student independence with the help of the Discovery Learning method on Humans as Persons in Phase E Class X and 2) Student independence with the help of the Discovery Learning method on Humans as Persons in Phase E Class X can achieve the expected targets. This research is a Classroom Action Research which consists of two cycles, each cycle consisting of four stages, namely planning, implementing, evaluating, and reflecting. The research subjects were Catholic students in class X Merdeka 1, totaling 13 people. The results of the study show that 1) Discovery Learning can increase learning independence in material for class X personal creatures of SMA Negeri 1 Putussibau. It can be seen that the average independence from 62.36% increased to 90.11%. 2) Discovery Learning can improve student learning outcomes in class X personal human beings at SMA Negeri 1 Putussibau. It can be seen that 38.5% is proficient, 30.8% proficient and 30.8% competent, increasing to 76.9% proficient, 23.1% proficient and 0% proficient. Thus it can be concluded that the Discovery Learning method is effective in increasing independence and learning achievement.